2009
DOI: 10.1002/ajh.21385
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine therapy in refractory/relapsed patients with thrombotic thrombocytopenic purpura

Abstract: To the editor: The interesting article by van Beers et al. states that functional studies does not offer clues as to the presence of mild pulmonary hypertension (PH) in patients with sickle cell disease (SCD) [1]. However, they did show that although not statistically significant, lung function findings do vary in hemoglobin-SS patients.Studies examining lung function in adults with SCD conclude that pulmonary function is abnormal in 90% of patients and gradually declines over time [2,3]. The most common patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 6 publications
0
18
0
2
Order By: Relevance
“…There are several reports describing the efficacy of CSA for either refractory TTP or as a prophylactic therapy to prevent relapse. 8,[20][21][22] Even though the prednisone-treated patients more quickly suppressed ADAMTS13 autoantibodies, the CSA-treated patients also showed suppression of the anti-ADAMTS13 antibodies, but took a longer time to achieve this result. The relatively longer time that was required for improvement in ADAMTS13 activity in the CSA arm may in part explain why it was less effective than the prednisone in this study, but still can be effective as a prophylactic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports describing the efficacy of CSA for either refractory TTP or as a prophylactic therapy to prevent relapse. 8,[20][21][22] Even though the prednisone-treated patients more quickly suppressed ADAMTS13 autoantibodies, the CSA-treated patients also showed suppression of the anti-ADAMTS13 antibodies, but took a longer time to achieve this result. The relatively longer time that was required for improvement in ADAMTS13 activity in the CSA arm may in part explain why it was less effective than the prednisone in this study, but still can be effective as a prophylactic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine A has been reported as an effective treatment in refractory TTP 19 and is also used as frontline treatment in association with TPE. The clinical response correlates with improvement in ADAMTS13 activity and suppression of anti-ADAMTS13 antibodies.…”
Section: Vincristine and Cyclosporine Amentioning
confidence: 99%
“…(23) and Nosari et al. (24, 25) recently showed that prophylactic cyclosporine is useful in preventing relapse when administered to patients with low ADAMTS13 activity and the presence of inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Knobl et al (22) reported the use of immunoadsorption, cyclophosphamide, and prednisone as an effective adjunct to plasmapheresis in refractory TTP, and suggested that fast and reliable assays for ADAMTS13 activity and inhibitor were necessary. Cataland et al (23) and Nosari et al (24,25) recently showed that prophylactic cyclosporine is useful in preventing relapse when administered to patients with low ADAMTS13 activity and the presence of inhibitors. Now that we have the serial measurements of ADAM-TS13 in TTP patients, it is clear that most patients achieve a tolerance state or normalize their enzyme levels; however, the tolerance can be broken, sometimes suddenly, such that low ADAMTS13 may represent a more fragile state than normal, leaving open the issue that perhaps some maintenance of tolerance is required.…”
Section: Immune Tolerance Inductionmentioning
confidence: 99%